Maternal and fetal characteristics of eclampsia at 2700 meters above sea level - Romero Castro, Ronnie Elkin (2015)
Introduction: Eclampsia is one of the most severe complications of preeclampsia in pregnancy. Objectives: To identify the epidemiological, clinical and maternal fetal complications of women suffering of eclampsia at 2 700 meters above sea level. Design: Descriptive study. Setting: Service of Gynecology and Obstetrics, Hospital Regional de Cajamarca, Peru. Participants: Women with diagnosis of eclampsia and their fetuses and newborns. Methods: Study of 28 cases of women with diagnosis of eclampsia of a total of 3 128 deliveries attended between January 2012 and December 2012, at 2700 meters above sea level. Main outcome measures: Maternal and fetal characteristics. Results: Incidence of eclampsia was 0.9%, one case for each 113 deliveries. Main age of women with eclampsia was 23.3 +- 6.5 years; 46.4% carried their first pregnancy, origin was rural in 71.4%; 46.4% had over 6 prenatal controls; in 53.6% blood pressure was >=160/110. Eclampsia occurred before delivery in 78.6%, and 71.4% needed cesarean section. The number of seizures was more than two in 74.7%. Most frequent symptom was headache in 89.2%. Creatinine was high in 35.7%, transaminases were increased in 39.2%, anemia was present in 64.3% and thrombocytopenia in 32.1%. Maternal complications were HELLP syndrome in 25% and maternal death in 3.4%. Perinatal complications were prematurity in 60.7%, intrauterine growth restriction in 39.3% and fetal death in 13.7%. Conclusions: Eclampsia at 2 700 m.a.s.l. was associated to important maternal and fetal morbidity and mortality.